PENGARUH KECERDASAN SPIRITUAL (SPIRITUAL QUOTIENT) TERHADAP KARAKTER RELIGIUS SISWA MTS NURUL IMAN DUSUN CITA HARAPAN DESA SUNGAI ARA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Liza Nurfadilah; Hambali '; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of code of the nation. One was the religious character of today's young generation. Spiritual Quotient has a role to influence the religious character of students. In this schools with a variety of activities to improve spiritual intelligence will affect the religious character of students. therefore, the formulation of the problem of this research is how the influence of spiritual quotient against the religious character of students MTs Nurul Iman Dusun Cita Harapan Sungai Ara Village District of Kempas Regency of Indragiri Hilir. The purpose of this study was to determine the influence of spiritual quotient against the religious character of students MTs Nurul Iman Dusun Cita Harapan Sungai Ara Village Distric of Kempas Regency of Indragiri Hilir. This research is useful for the reader to add insight and information about education. This research method is quantitative descriptive. Data collection instruments used were a questionnaire consisting of 25 statements about spiritual quotient (variable X) and 25 statement about religious character (variable Y) distributed to 58 student respondents. Data analysis using simple linear regression. Thus the hypothesis that